Catch Composition and Selectivity Drift Gillnet in Pambang Pesisir Village Bantan Subdistrict Bengkalis Regency - Anggraita, Dea Virgin; Bustari, Bustari; Nasution, Polaris (Tropical Marine Environmental Sciences, 2024)
Gill nets are placed perpendicular to the water to block the swimming direction of the fish. Fish are caught by being entangled in the meshes or entangled (spun) in the body of the net. This research was conducted in Pambang Pesisir Village, Bantan District, Bengkalis Regency, to know the composition of the catch and the selectivity of drift gill nets, comparing the composition of the number, type, weight, and size of the catch from different mesh sizes, and knowing how to catch fish (entangled, gilled, snagged, wedged) on the same mesh used. This research was carried out in December 2020 using the experimental fishing method, which is a research method that uses samples of research objects caught on fishing gear for observation. The research results of drift gill nets are species-selective fishing gear. Moreover, drift gill nets with a mesh size of 7.62 cm are more selective than nets of 5.72 cm because they have a catch ratio value closer to 1 and catch more large fish (worth catching). How to catch fish with a mesh size of 5.72 cm, many fish were caught by snagged; namely, 65 fish (30%), wedged 61 fish (28%), gilled 59 fish (27%), and 33 fish entangled (15%). Meanwhile, for the mesh size of 7.62 cm, 30 fish (31%) were caught wedged, 27 fish (29%) snagged, 27 fish (29%) gilled, and ten fish entangled (11%).